PENGARUH EDUKASI DENGAN MEDIA FLASHCARD TERHADAP PENGETAHUAN KONSUMSI TABLET TAMBAH DARAH PADA REMAJA DI SMP NEGERI 1 GODEAN - Hanifa Salsabila Putu Yahya; Esitra Herfanda (Rena Cipta Mandiri, 2026)
Anemia remains a public health problem among adolescent girls, including in Sleman Regency, with a prevalence of 14.43% in 2024, despite the coverage of Iron Supplement Tablet (IST) consumption reaching 95.03%. This condition indicates that the high coverage of IST distribution has not been fully accompanied by adequate knowledge among adolescent girls regarding correct and appropriate IST consumption practices. Therefore, more effective and engaging health education efforts are needed to improve adolescent girls’ understanding of IST consumption as an early preventive measure against anemia. This study aims to determine the effect of flashcard-based education on knowledge of IST consumption among adolescent girls at SMP Negeri (State Junior High School) 1 Godean. This study employed a quantitative method with a pre-experimental one-group pretest–posttest design. The sample consisted of 43 eighth-grade female students selected through simple random sampling technique. Data were collected using a knowledge questionnaire administered before and after the flashcard-based educational intervention. The results showed an increase in adolescent girls’ knowledge levels following the intervention. A significant difference in knowledge was observed before and after the education, with a p-value of 0.002 (p < 0.05), indicating that flashcard-based education had a significant effect on knowledge of Iron Supplement Tablet consumption. In conclusion, flashcard media can be utilized as an alternative health education tool in schools to support anemia prevention efforts from adolescence.